Behavior Users of E-Money for Payment in E-Toll Based on Assessment Technology Acceptences Model - Laksmia, Anisha Ayu (Jurnal Ilmiah Mahasiswa FEB, 2018)
The objective of this research is to know and analyze the influence of Ease of Use Perceived, Convenience Perceived, Quality of Service Provider,and Security Perceived to user behavior in using E-Money on E-Toll payment. The theory used in this research is Technology Acceptences Model. Data source used in this research is primary data. This study used the method of online questionnaire survey through Googleform which was distributed to 151 respondents who came from the students of Accounting Department Force 2015-2017 Faculty of Economics and Business Brawijaya University. The analysis technique used is factor analysis and multiple linear regression. In this research using SPSS 2.3 software to test the research data. The results showed that the influence of ease of use perceived, convenience perceived, quality of service provider, security perceived gave positive and significant influence to E-Money user behavior on E-Toll payment. The more modern technological developments in finance can improve the economy in Indonesia and simultaneously with the increasing ability of community acceptance of technological developments using E-Money on E-Toll payments.Keywords: Consumer Behavior, TAM, E-Money, E-Toll